ANALYSIS OF EQUIPMENT THE BUS STOPS ABROAD - Jurkovicova, Hana (Doprava a spoje, 2012)
The article deals with the analysis of equipment of stops abroad. Processed are selected types of stops abroad, especially intelligent stops, solar bus stops, barrier-free modified bus stops. In the article is also processed a new type of bus stop EBSF that provides passengers comfort, safety, possibility of using wifi connection and various information about traveling and tourism in the city.